Prateći objekti i širi turistički sadržaji uz Jadransku autocestu - MALIĆ, Adolf; TOPOLNIK, Dražen (Promet - Traffic&Transportation, 2026)
ACCOMPANYING FACILITIES AND BROAD-SCOPE TOURIST FACILITIES ALONG THE ADRIATIC HIGHWAY The authors consider the meaning and importance of the planned Adriatic highway (expressway) and which particular accompanying facilities and broad-scope tourist facilities are planned for construction. The paper expounds on the planned conditions of construction and project or program concept as well as the financial structure, anticipated funding sources and strong requirement of participation of foreign capital on a sound commercial basis. Particular reference has been made to the requirement of construction and/or modernization of accompanying transversal traffic routes in the mainland parts leading to the coastal region.